# Given that f(x) = 5x - 10 and g(x) = x + 3, solve for f(g(x)) when x = -1.

-30, 0, 10, 12

**Solution:**

g(x) = y\(_1\)_{ }= x + 3 ….. (1)

f(x) = y\(_2\)_{ }= 5x - 10 ….. (2)

f(g(x)) is a composite function can be written as (fog)(x)

Where x is present in f(x) you should substitute y\(_1\)_{ }

I.e., substituting equation (1) in x which is present in equation (2)

f(g(x)) = 5 y\(_1\)_{ }- 10 where y\(_1\)_{ }= x + 3

f(g(x)) = 5 (x + 3) - 10

f(g(x)) = 5x + 15 - 10

f(g(x)) = 5x + 5

Now substitute x = -1 in f (g(x))

f(g(-1)) = 5 (-1) + 5

So we get

f(g(-1)) = -5 + 5 = 0

Therefore, f(g(x)) when x = -1 is 0.

## Given that f(x) = 5x - 10 and g(x) = x + 3, solve for f(g(x)) when x = -1.

-30, 0, 10, 12

**Summary:**

Given that f(x) = 5x - 10 and g(x) = x + 3, f(g(x)) when x = -1 is 0.

Math worksheets and

visual curriculum

visual curriculum